SYNTACTIC VARIATION IN MASORETIC HEBREW, THE OBJECT CLAUSE RECONSIDERED - Naaijer, Martijn; Roorda, Dirk (Journal for Semitics, 2017)
In this article we reinvestigate the variation in Masoretic Hebrew of two linguistic features related to the object clause that have diachronic relevance according to various scholars. These features are the order of subject personal pronoun and nominal predicate in certain object clauses, and the variation between ×›×™ and ××©×¨ introducing the object clause. We do this by using tools provided by the SHEBANQ project. By examining as many cases as possible throughout the Masoretic Text instead of only a few exemplary cases, we analyse the extent of variation in these syntactic constructions and their relevance for linguistic dating of biblical texts.